A Content Analysis of Indonesian Cultures in the English Textbook ‘My Next Words’ 5th Grade - Olga Anzala Sakinata (The Faculty of Teacher Training and Education, 2023)
Language and culture are interconnected, as language not only facilitates communication but also conveys cultural identity and values (Brown, 2007). Learning a new language involves understanding the associated culture, which includes tangible and intangible components. In learning English, English textbooks are essential tools and cultural exposure, especially at the elementary level, where they help students build English proficiency while fostering cultural awareness, including an understanding of Indonesian culture (Chung & Long, 2024; Faridatunnisa, 2020). The emancipated curriculum (Kurikulum Merdeka) allows the integration of local content, promoting students’ connection to their cultural heritage and nationalism. Stories regarding daily life activities, traditions, and norms may be included. Therefore, this research aims to discover Indonesian cultural elements embedded within an English textbook entitled “My Next Words” in the 5th grade. In this study, the learning materials in the form of visual images were analyzed using Yuen’s (2011) cultural dimensions.
februari 2026 Rudi H
Keywords: A Content Analysis; f Indonesian Cultures; the English Textbook; My Next Words